Decision-making support system for beef cattle carcass quality using fuzzy modeling - Silva , Allan Leon Casemiro da; Gabriel, Camila Pires Cremasco; Putti, Fernando Ferrari; Chacur, Marcelo George Mungai; Gabriel Filho, Luís Roberto Almeida (Electronic Journal "Fórum Ambiental da Alta Paulista", 2022)
Carcass assessment by slaughterhouses is as important as an efficient production of quality animal. The evaluation is performed subjectively by individuals although it follows delimited criteria. Therefore, an expert system should be developed to allow both reduction of subjectivity in analysis and valuation with more complex and non-continuous variables. This chapter aimed at developing a decision-making support system to assess beef cattle carcass in slaughterhouses, using a fuzzy logic modeling. The subjective knowledge of experts on beef cattle carcasses quality was used to build membership functions. Animal maturity, weight, and fatness degree were used as quality indicators, but quality itself was an output variable. The proposed fuzzy model showed 89.5% compatibility with the scores of the experts and allowed a higher specificity of the presented score, reducing differences between classifications.